التكيف الاجتماعي لدى عينة من أطفال التوحد أربع حالات في ولاية الأغواط - عاجب بومدين (My University, 2019)
Through the field study, we chose four cases that are present in the psychological center in the state of Laghouat and all cases are close to 10 to 11 years old. The diagnostic scale has been applied to these four cases and through it to the case of Qweider and Ahmad a minor autism. Both Hussain and Asil are very sharp. Qweider is different from the rest of the cases because he responds to instructions and this is what the supervisor said he does not suffer from Autism, however, that the interruption of the center for a long time a back to back, although he was superior to the rest of the cases. Thus, each case is different from the other through the symptoms and this is the degree of social adjustment in each case.